Medicolegal Evaluation of Patients with Thermal Burns - Karabağ, Gökmen; Can, İsmail Özgür; Demiroğlu Uyanıker, Zehra; Vayvada, Haluk (The Bulletin of Legal Medicine, 2021)
Objective: The aim of this study was to improve the criteria used in the medicolegal evaluations of patients with thermal burns and to make recommendations on the subject, based on the Burn Center Referral Criteria of the American Burn Association.Methods: The patients acutely affected by thermal burns and admitted to Dokuz Eylul University Hospital, Ataturk Training and Research Hospital and Dr. Behcet Uz Child Disease and Pediatric Surgery Training and Research Hospital in one year period were investigated in terms of age, gender, burn type, burn depth, affected body area, referral status to burn center and medicolegal evaluation results.Results: It was observed that 314 (53.4%) of 588 patients were male, and the mean age was 20.68 ± 21.30 years. According to the burn types, 485 (82.5%) patients burned by contact with hot liquids, 74 (12.6%) patients burned by contact with flame, and 29 (4.9%) patients burned by contact with hot solid objects. The rate of burning with hot liquids was found to be higher in female patients compared to male patients. The mean percentage of total body surface area (TBSA) burned was 6.06 ± 6.40%.Conclusion: It was concluded that it would be more appropriate for burns of special areas to increase the severity of the clinical condition and to include different age groups such as the 0-5 age group, 6-15 age group and age group over 65 years instead of the 5-year age limit in medicolegal evaluations.
Keywords: Burn; forensic medicine; medicolegal evaluation; burn center referral criteria